Different Concentrations of Lactobacillus acidophilus Cell Free Filtrate Have Differing Anti-Biofilm and Immunomodulatory Effects - Wilson, Rachael M.; Walker, Jean M.; Yin, Kingsley (Frontiers in Cellular and Infection Microbiology, 2021)
Probiotics such as various strains of Lactobacillaceae have been shown to have antimicrobial and immunomodulatory activity. In vitro studies have shown that Lactobacilli can decrease bacterial biofilm formation. Effects on immune cells have been unclear with most studies showing anti-inflammatory activity. The mechanism of effects has not been clearly elucidated. In these studies, we used different concentrations of live Lactobacillus acidophilus as well as cell free filtrate (CFF) derived from different concentrations of bacteria. Use of CFF is advantageous as a therapeutic because in vivo it can directly contact immune cells and its concentration is fixed. Both live cells and CFF inhibited Pseudomonas aeruginosa biofilm formation. Importantly, we show that high concentration CFF destroyed mature biofilm. This activity was not due to a lowered pH per se, as pH matched HCl did not remove mature biofilm. High concentration CFF totally inhibited P. aeruginosa growth and was bactericidal (>99.99%), but low concentration CFF was not bactericidal. To examine the immunomodulatory effects of L. acidophilus, we incubated THP-1 monocytes and derived macrophages with CFF and measured TNFα production. CFF did not significantly increase TNFα production in THP-1 monocytes. When cells were prestimulated with LPS, high concentration CFF increased TNFα production even further. In macrophages, high concentration CFF alone increased TNFα production but did not affect LPS prestimulated cells. In contrast, low concentration CFF decreased TNFα production in LPS prestimulated cells. To elucidate the possible mechanisms for these effects, we repeated the experiments using a NF-κB reporter THP-1 cell line. High concentration CFF increased NF-κB activity in monocytes and macrophages. In LPS prestimulated macrophages, only low concentration CFF reduced NF-κB activity. These results suggest that high concentration CFF alone induced NF-κB expression which could account partially for an increase in TNFα production. On the other hand, in macrophages, the lower non-bactericidal concentration of CFF reduced NF-κB expression and decreased TNFα production after LPS prestimulation. Taken together, the results provide evidence that different concentrations of L. acidophilus CFF possess varying bactericidal, anti-biofilm and immunomodulatory effects. This is important in vivo to evaluate the possible use of L. acidophilus CFF in different conditions.